Clinical Significance of Tumor Location for Ureteroscopic Tumor Grading in Upper Tract Urothelial Carcinoma - Katayama, Satoshi; Pradere, Benjamin; Grossman, Nico C; Potretzke, Aaron M; Boorjian, Stephen A; Ghoreifi, Alireza; Daneshmand, Siamak; Djaladat, Hooman; Sfakianos, John P; Mari, Andrea; Khene, Zine-Eddine; D'andrea, David; et al. (Journal of endourology, 2024)
Background: Although previous literature shows tumor location as a prognostic factor in upper tract urothelial carcinoma (UTUC), there remains uninvestigated regarding the impact of tumor location on grade concordance and discrepancies between ureteroscopic (URS) biopsy and final radical nephroureterectomy (RNU) pathology. Methods: In this international study, we retrospectively reviewed the records of 1,498 patients with UTUC who underwent diagnostic URS with concomitant biopsy followed by RNU between 2005 and 2020. Tumor location was divided into four sections: the calyceal-pelvic system, proximal ureter, middle ureter, and distal ureter. Patients with multifocal tumors were excluded from the study. We performed multiple comparison tests and logistic regression analyses. Results: Overall, 1,154 patients were included; 54.4% of those with low-grade URS biopsies were upgraded on RNU. In the multiple comparison tests, middle ureter tumors exhibited the highest probability of upgrading, meanwhile pelvicalyceal tumors exhibited the lowest probability of upgrading (73.7% vs 48.5%, p = 0.007). Downgrading was comparable across all tumor locations. On multivariate analyses, middle ureteral location was significantly associated with a low probability of grade concordance (odds ratio [OR] 0.59; 95% confidence interval [CI], 0.35-1.00; p = 0.049) and an increased risk of upgrading (OR 2.80; 95% CI, 1.20-6.52; p = 0.017). The discordance did not vary regardless of caliceal location, including the lower calyx. Conclusions: Middle ureteral tumors diagnosed to be low grade had a high probability to be undergraded. Our data can inform providers and their patients regarding the likelihood of undergrading according to tumor location, facilitating patient counseling and shared decision making regarding the choice of kidney sparing vs RNU.
Keywords: biopsie; Biopsy; Aged; Nephroureterectomy; Aged, 80 and over; Retrospective Studies; lidé středního věku; senioři; Clinical Relevance; Carcinoma, Transitional Cell; lidé; Middle Aged; nefroureterektomie; Female; senioři nad 80 let; Ureter; Male; ženské pohlaví; Neoplasm Grading; Ureteral Neoplasms; Humans; klinická relevance; mužské pohlaví; ureteroskopie; nádory ledvin; ureter; stupeň nádoru; nádory močovodu; Kidney Neoplasms; Ureteroscopy; karcinom z přechodných buněk; retrospektivní studie